FORMULATION AND EVALUATION OF CYCLODEXTRINS BASED CARVEDILOL SOLID INCLUSION COMPLEXES BY LYOPHILIZATION METHOD - GITA CHAURASIA (International Journal of Pharma and Bio Sciences, 2013)
Cyclodextrins are cyclic (α-1, 4)-linked oligosaccharides β-D-glucopyranose containing a relatively hydrophobic central cavity and hydrophilic outer surface, which have been extensively used to increase aqueous solubility of carvedilol (CVD). The phase solubility of the drug indicated the formation of 1:1 Molar and 1:2 Molar inclusion complexes in solution with β-cyclodextrin (β-CD) and 2-hydroxy-propyl-β-cyclodextrin (HP-β-CD). The solid complexes were prepared by Lyophilization method and characterized by differential scanning calorimetry (DSC), FTIR, Scanning electron microscopy (SEM) and UV-Spectrophotometry. Complexes were analyzed for drug content and the increment in the aqueous solubility. Carvedilol was found to be 17.5 times and 34.16 times greater in β-CD-CVD complex and HP-β-CD-CVD complex (in 1:2 Molar) respectively, than pure drug alone. The solubility of HP-β-CD-CVD in 1:1 Molar was found to be 2.05 times increment than β-Cyclodextrin-drug complex and 1.952 times more in HP-β-CD-CVD complex in 1:2 Molar than β-CD-CVD complex. Thus, the cyclodextrins provided significant increment in aqueous solubility of drug molecule.